2017
DOI: 10.1093/nar/gkx266
|View full text |Cite
|
Sign up to set email alerts
|

Replication and repair of a reduced 2΄-deoxyguanosine-abasic site interstrand cross-link in human cells

Abstract: Apurinic/apyrimidinic (AP) sites, or abasic sites, which are a common type of endogenous DNA damage, can forge interstrand DNA–DNA cross-links via reaction with the exocyclic amino group on a nearby 2΄-deoxyguanosine or 2΄-deoxyadenosine in the opposite strand. Here, we utilized a shuttle vector method to examine the efficiency and fidelity with which a reduced dG–AP cross-link-containing plasmid was replicated in cultured human cells. Our results showed that the cross-link constituted strong impediments to DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 43 publications
(71 reference statements)
0
23
0
Order By: Relevance
“…Among the most potent blocks to replication are interstrand crosslinks (ICLs). They are formed by highly toxic cancer chemotherapy drugs and DNA reactive compounds generated during normal cellular metabolism, including lipid peroxidation products (Niedernhofer et al, 2003), aldehydes (Pontel et al, 2015), and abasic sites (Price et al, 2017). ICLs are of additional interest because of the hyper-sensitivity to them of cells from patients with Fanconi anemia (FA).…”
Section: Introductionmentioning
confidence: 99%
“…Among the most potent blocks to replication are interstrand crosslinks (ICLs). They are formed by highly toxic cancer chemotherapy drugs and DNA reactive compounds generated during normal cellular metabolism, including lipid peroxidation products (Niedernhofer et al, 2003), aldehydes (Pontel et al, 2015), and abasic sites (Price et al, 2017). ICLs are of additional interest because of the hyper-sensitivity to them of cells from patients with Fanconi anemia (FA).…”
Section: Introductionmentioning
confidence: 99%
“…Studies using the bacteriophage ϕ29 DNA polymerase demonstrated that if not repaired, these ICLs block replication . The reduced dG-AP ICL required multiple polymerases for bypass and was mutagenic …”
mentioning
confidence: 99%
“…Importantly, AP sites are chemically labile and reactive and can lead to secondary DNA damage such as DNA single-strand breaks (SSBs), DNA-DNA interstrand cross-links, and DNAprotein cross-links (DPCs) (18)(19)(20)(21)(22)(23). If not repaired, AP sites and their derivatives are mutagenic in the nuclear genome (24)(25)(26); however, the understanding of the biological consequence of AP sites in mitochondria remains limited.…”
mentioning
confidence: 99%